Factors that contributes to the on-time delivery performance of Hicom Diecasting Sdn Bhd, Shah Alam / Nursyahida Rosli - Rosli, Nursyahida (Faculty of Business and Management, 2010)
According to the topic chosen, on time delivery (OTD) is one of the key performance indicators (KPI) of the Hicom Diecasting, Shah Alam. Research objectives for this study undertaken are to identify the most frequent evaluations of dependent variables, to identify the ranking evaluation on the independent variables, identify the major contributors for of non-on time delivery and to recommend improvement or solutions in this research. The scope of the study is mainly focusing on the evaluation of implementation to reduce non-on the time delivery of production department, Hicom, Shah Alam. A set of questionnaires was distributed to the respective respondents. Several factors that being discussed in this research are demographic, 4M elements that contribute to the performance of on time delivery which are Manpower, Material, Machine and Method. The data is analyzed using descriptive analysis, frequency, and coefficients of Statistical Package for Social Sciences (SPSS).